HUBUNGAN FAKTOR INDIVIDU DAN ORGANISASI DENGAN KINERJA TENAGA KESEHATAN PADA PROGRAM PPIA - Kusuma, Devi (Universitas Tadulako, 2024)
Transmission of HIV infection from pregnant women to babies can be prevented with the Prevention of HIV Transmission from Mother to Child (PPIA) Program. However, in its implementation, four Community Health Centers in Gresik Regency have not met HIV testing requirements. Therefore, to achieve these standards, a study of the factors that influence the performance of the PPIA workforce is required. This research aims to identify factors that influence the performance of PPIA workers. Data were collected using a total sampling technique using a questionnaire on a sample of 45. Next, hypothesis testing was carried out. The research results show that most PPIA workers at the Gresik Regency Health Center perform poorly, while their knowledge tends to be low. There is no significant relationship between length of service, motivation, or leadership and the performance of the PPIA workforce. This indicates problems in understanding, motivation, and leadership in the work environment. Improvement efforts, such as designing human resource management (HR) strategies and developing the health workers' competencies, are needed. The results of this research can be used to design strategies to increase human resources to increase HIV testing outcomes for pregnant women and reduce HIV transmission from pregnant women to babies.